2008
DOI: 10.1002/14651858.cd002977.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Devices and pressure sources for administration of nasal continuous positive airway pressure (NCPAP) in preterm neonates

Abstract: Devices and pressure sources for administration of nasal continuous positive airway pressure (NCPAP) in preterm neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(105 citation statements)
references
References 57 publications
(1 reference statement)
1
102
0
2
Order By: Relevance
“…To our knowledge, this is the first and largest study to investigate the effects of different NCPAP interfaces on BPD where the RDS patients were treated with less invasive surfactant administration. In a Cochrane meta-analysis [12], the effect of the technique of pressure generation and the type of nasal interface for NCPAP delivery to effectively reduce the need for additional respiratory support was studied; only 1 trial identified preterm infants primarily treated with NCPAP soon after birth. Mazzella et al [25] found a significantly lower oxygen requirement and respiratory rate in infants randomized to short NP than to CPAP delivered via nasopharyngeal prong.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first and largest study to investigate the effects of different NCPAP interfaces on BPD where the RDS patients were treated with less invasive surfactant administration. In a Cochrane meta-analysis [12], the effect of the technique of pressure generation and the type of nasal interface for NCPAP delivery to effectively reduce the need for additional respiratory support was studied; only 1 trial identified preterm infants primarily treated with NCPAP soon after birth. Mazzella et al [25] found a significantly lower oxygen requirement and respiratory rate in infants randomized to short NP than to CPAP delivered via nasopharyngeal prong.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used to deliver NCPAP are prongs (NP) and masks (NM). Short binasal prongs seem to be more effective than a single NP or nasopharyngeal prongs because of the reduced resistance in the nares [11,12]. Masks that fit over the nose were developed many years ago and are commonly used today [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In comparing the non-invasive ventilation with NIPPV to the nasal CPAP, fewer respiratory failures and the need for intubation in the NIPPV group were found [46]. Meta-analysis of the use of different devices and interfaces for CPAP has elucidated differences in outcome depending on the use of nasal adapters or interfaces, requiring further research [47]. Similarly, there is an open question whether breathing with the help of bi-level CPAP is better than breathing with CPAP alone and does it pose an advantage of better exhaling CO 2 , better oxygenation or other physiological indicators [48].…”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%
“…Se ha utilizado para tratar la apnea frecuentes o graves en los niños prematuros, los informes de casos de perforaciones gastrointestinales ha limitado su uso generalizado, parece reducir la frecuencia de apneas de manera más eficaz que el CPAP, se necesita más datos acerca de la seguridad y eficacia antes de recomendar la VNPPI como 3; N° 3; Diciembre 2016 (38) tratamiento estándar en las apneas . La Academia American de Pediatría (AAP) y la Asociación American del Corazón (AHA) recomienda lo siguiente con relación al uso de O en 2 (39) la reanimación .…”
Section: Ventilación Con Presión Positiva Intermitente Nasal (Vnppi)unclassified